Axial load of built-up sigma section cold formed steel with hole - Nuradibah, Mohammad Zin (2019)
The objective of this paper is to determine the maximum load of open built-up steel and to study the built-up sigma section cold-formed steel with hole. Cold-formed steel commonly used as compression members to carry heavier loads. The column specimens were compressed between bearing plate with flat ends. Two series of E-section will be used which is BE103-2.0 and also BE203-2.0. All specimens with same height of 600 mm with two without opening and the other 6 with different position of openings from support. The shape of openings that have been used for all specimen is same which is elongated. This experiment is testing by using Universal Testing Machine (UTM). During the experiment, three transducers is used and been located at the specimen. The function of transducer is to read the displacement of the specimen during testing where the graph had been plotted. The opening distance from the support and specimen without opening will show a difference of the results. After the test, local buckling and distortional buckling can be seen at the specimen. Most of the specimen without opening shows the maximum load compared to the specimen with opening.